การประเมินมูลค่าความเต็มใจที่จะจ่ายเพื่อสนับสนุนให้องค์การ บริหารส่วนตำบลขนาดเล็กจัดสิ่งแวดล้อมศึกษาในการจัดการ ขยะครัวเรือน - ภาคพิธเจริญ, อารีรัตน์; มาดิลกโกวิท, จรูญศรี; เพชรานนท์, โสมสกาว (Journal of Education Studies, Chulalongkorn University, 2014)
การวิจัยนี้เป็นการประเมินมูลค่าความเต็มใจที่จะจ่ายโดยใช้รูปแบบเหตุการณ์สมมุติ ในพื้นที่ องค์การบริหารส่วนตำบลขนาดเล็ก ๔ แห่ง เก็บรวบรวมข้อมูลโดยใช้คำถามปลายปดิ แบบ ๒ ขนั้ และ วิเคราะห์สมการถดถอยโดยใช้รูปแบบฟังก์ชัน Lognormal ผลการศึกษาพบว่า มูลค่าความเต็มใจที่จะ จ่ายเงินบริจาคเพื่อสนับสนุนการจัดสิ่งแวดล้อมศึกษาในการจัดการขยะครัวเรือนขององค์การบริหาร ส่วนตำบลขนาดเล็กมีค่าเฉลี่ยและค่ามัธยฐานเท่ากับ ๒๙๗.๔๗ และ ๒๕๗.๕๓ บาทต่อครัวเรือนต่อปี ตามลำดับ มูลค่าของประโยชน์จากการจัดสิ่งแวดล้อมศึกษาอยู่ในช่วง ๒,๔๕๐,๓๓๓.๒๑ - ๒,๘๑๔,๓๔๕.๕๐ บาทต่อปี เมื่อพิจารณาปัจจัยพบว่า ค่าเริ่มต้น ระดับการศึกษา และการรับรู้ข้อมูลงบประมาณในการจัดการ ขยะชุมชนมีความสัมพันธ์ในทิศทางเดียวกับความเต็มใจที่จะจ่ายที่ระดับความเชื่อมั่นร้อยละ ๙๙ ในการ ศึกษานี้จึงเสนอให้องค์การบริหารส่วนตำบลขนาดเล็กลงทุนทักษะความรู้เพื่อพัฒนาคนในชุมชนให้เกิด รายได้เพิ่มขึ้นควบคู่กับการลงทุนจัดสิ่งแวดล้อมศึกษา และควรคืนข้อมูลงบประมาณและประโยชน์จาก การลงทุนผ่านเวทีประชาคมหรือสื่อชุมชนอย่างชัดเจนและต่อเนื่อง This study aimed to determine the value of willingness to pay (WTP), using a simulation model approach in a case study of 4 small sub-district administrative organizations (SSAO). The data were collected using double bounded close-ended questions. Censored logistic regression in the distribution function of the Lognormal was used for data analysis. The results showed that the mean and the median WTP for donating money to SSAO environmental education to support household solid waste management (HSWM) is worth 297.47 and 257.53 baht per household per year, respectively. The value of utilization obtained from environmental education ranged from 2,450,333.21 to 2,814,345.50 baht per year. With respect to factors affecting WTP value, it was found that the stating bid, the levels of education and the reception of information on of the HSWM budget showed a positive relationship with WTP at the reliability level of 99%. This research indicated that the major investment of SSAO should be in the knowledge and skill enhancement for community members to increase household income, together with investment in the environmental education provision. In addition, the SSAO should return budget information and investment benefits through a community forum and the media clearly and continuously